Analysis on the behavior of wireless sensor node through test-bed implementation / Yusnani Mohd Yussoff ... [et al.] - Mohd Yussoff, Yusnani; Zainol Abidin, Husna; Ab Rahman, Ruhani; Yahaya, Faeiza Hanum (Institute of Research, Development and Commercialization , Universiti Teknologi MARA, 2011)
Wireless Sensor Networks (WSN) has fundamentally different architecture than normal wired data networks. They are highly constrained in resources, have multi-hop wireless connectivity and form Ad hoc networks with random deployment in possibly unmanned terrain. The sensor nodes are usually scattered in a sensor field. Each of the sensor nodes has the capabilities to collect data and route the data back through a multi-hop hybrid wireless communication. The design of sensor network is influenced by many factors including scalability, operating system, fault tolerance, sensor network topology, hardware constraints, transmission media and power consumption. The assessment of performance in wireless sensor network is generally difficult since mathematical models are based on assumptions and simplifications. In order to develop an appropriate protocol for a given application, appropriate network conditions must be used and metrics of the intended WSN application must be taken into consideration. Network (wireless and wired) currently fully depend on infrastructure to enable the communication. An alternative method for these issues is wireless sensor network that utilize Ad hoc network communication characteristics. Test bed implementation is a must before studies or applications development in wireless sensor network can be initiated. This project will concentrate on setting up a working wireless sensor network test bed that will have the capabilities to transfer data and communicate with each other and with a central server.